Research Report on the Overseas Network Communication Power of Northwest Chinese Universities under the Background of the “Double First-Class” Initiative - Fan, Chenyang; Huang, Jiayang; Xu, Kaiming; Wang, Yinuo; Yu, Ziying (Journal of Educational Research and Policies, 2025)
With the increasing importance of national image in national strategic construction, the Double First-Class Initiative of “building first-class universities and disciplines of the world” has attracted widespread social attention. Under this background, shaping a good brand image of universities has become one of the core tasks of “Double First-Class” university construction and an important way to enhance China’s international competitiveness in higher education. This study selected 12 “Double First-Class” universities in Northwest China and compared them with the top 12 international universities in the 2022 QS ranking. Based on data scraping and analysis of major overseas social platforms, and focusing on dimensions such as communication channels, content, and effects, a scientific evaluation index system and algorithm model were constructed to systematically assess the current situation of overseas network communication power of “Double First-Class” universities in Northwest China. The research found that the “Double First-Class” universities in Northwest China face several main problems in their overseas network communication construction: Firstly, there is a general lack of systematic and forward-looking awareness of overseas communication, resulting in the failure to convey important information about the universities’ development in a timely and effective manner. Secondly, the operation of multiple accounts and projects leads to redundancy and duplication, and there is a lack of a unified channel for communication, resulting in low communication efficiency. Thirdly, the promotional content is monotonous, and the universities have not fully utilized diverse communication forms such as videos and interactive content, making it difficult to enhance the appeal and effectiveness of their communication. Fourthly, the mechanism for public opinion risk prevention and control is not sound, and the universities lack the ability to respond quickly and effectively to overseas public opinion crises. In response to these problems, the research team proposed the following optimization strategies: Firstly, strengthen the accuracy and timeliness of information dissemination, establish an efficient information update mechanism, and ensure that the latest developments of the university can cover the target audience in a timely manner to enhance the value of information dissemination. Secondly, optimize the integration and unification of communication channels, reduce redundancy through centralized management, and enrich the forms of communication, focusing on the comprehensive use of pictures, videos, live broadcasts, and other media to enhance the diversity and attractiveness of communication content. Finally, build a sound public opinion risk prevention and control mechanism, establish a dedicated emergency response team and crisis management process, and improve the rapid response capabilities to overseas public opinion crises, so as to better maintain the reputation and image of the university. This study not only revealed the core bottlenecks in the construction of overseas network communication power of “Double First-Class” universities in Northwest China but also provided data support and theoretical basis for their brand building and image promotion. The research results are of great reference value for promoting the further integration of Northwest China’s universities into the international higher education system, enhancing their international communication capabilities and brand influence. At the same time, the study provided inspiration for the international communication strategies of “Double First-Class” universities across the country, aiming to help China’s higher education achieve greater breakthroughs and development in global competition.